Changes in the quality of life and nutrition markers in transition from end-stage kidney disease to kidney transplantation: insights from a Vietnamese cohort - Nguyen, Thu Ha; Mohd, Rozita; Mat Daud, Zulfitri 'Azuan; Abd Talib, Ruzita; Poh, Bee Koon (Springer Science and Business Media LLC, 2024)
Background: Malnutrition is strongly associated with lower quality of life (QoL) and lower survival rates in patients with end-stage kidney disease. However, the impact of renal transplantation on nutrition factors and QoL is unclear. Therefore, this study aims to assess changes in QoL and investigate the relationships with nutrition factors among kidney transplant recipients (KTRs). Materials and methods: A longitudinal study included 86 dialysis patients aged 18-65 years who underwent primary kidney transplantation (KTx) and were followed up for one year. Body weight, biochemical parameters, and QoL data were collected before transplantation (T0) and at six months (T6) and 12 months (T12) post- transplantation. Effect size (ES) was used to measure the impact of KTx on QoL and nutritional status from T0 to T12. The predictors of QoL were calculated with β-coefficients and p<0.05 in linear regression. Results: The ES of transplantation on the QoL of KTRs was large, at 1.1 for health change, 0.9 for physical health, and moderate (0.7) for mental health (MH) over one year. Hemoglobin and malnourished were affected by KTx, with ES being 2.4 and 0.6, respectively. Linear regression showed that physical health was predicted by hemoglobin (β=0.12, p<0.01), phosphorus (β=7.82, p<0.05), and dose of mycophenolate mofetil (MMF) (β=- 0.01, p<0.05). Mental health was predicted by obesity (β=-7.63, p<0.05), hemoglobin (β=0.11, p<0.05), and phosphorus (β=8.49, p<0.01). Health change was indicated by nutritional risk index (NRI) score (β=0.47, p<0.05), total cholesterol (β=3.39, p<0.01), and kidney function (β=0.15, p<0.05). Conclusions: The transition from end-stage kidney disease to transplantation has positive impacts on QoL and nutrition markers. Nutritional status, kidney function, and the dose of mycophenolate mofetil are significant determinants of QoL in KTRs.